Exploring the Impact of Deformation on Strain Energy of Ultrafine-Grained Copper through Equal Channel Angular Pressing: Insights from X-Ray and Neutron Diffraction - Muhammad Rifai; Mujamilah Mujamilah; Andon Insani; M. Refai Muslih; Tri Hardi Priyanto; Iwan Sumirat; Bharoto Bharoto; Grace Tj. Sulungbudi; Ahadi Damar Prasetya; Ridwan Ridwan; Muhamad Saparudin; Diene Noor H.; Sairun Sairun; Rifky Apriansyah; Wildan Z. Lubis (Directorate for Research and Innovation (DRI) ITB, 2026)
The mechanical behavior of materials at the nanoscale level has attracted significant attention in materials science research. This study investigated the impact of deformation on the strain energy of ultrafine-grained (UFG) copper produced by equal channel angular pressing (ECAP). X-ray and neutron diffraction techniques were employed to analyze the changes in strain energy of the copper samples subjected to varying levels of deformation. The results of the study indicate that the strain energy of the UFG copper increased with increasing levels of deformation due to the formation of dislocations with high density in the copper crystal structure. The study also found that the increase in strain energy was more significant in the initial stages of deformation and then reached a plateau as deformation progressed. This study provides valuable insight into the mechanical behavior of UFG copper and the role of deformation in altering its strain energy. The results can contribute to developing new materials with improved mechanical properties for various aerospace, automotive, and biomedical applications. The study highlights the importance of using advanced techniques such as X-ray and neutron diffraction to accurately investigate the nanoscale mechanical behavior of materials.